(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Gastroretentive drug delivery with delayed release of propranolol hydrochloride for chronotherapy of hypertension was formulated. The drug delivery in the form of compression coated tablet was developed using Indian Pharmacopoeia grade hydroxypropyl methyl cellulose K100M and carbopol 934P as matrix forming polymers and polyvinyl pyrrolidone K30 as channelling agent. Drug-excipient compatibility study revealed no interaction between drug and the excipients. Prepared tablets were evaluated for floating lag time, total floating time and lag time before drug release. Drug delivery was optimized by using 32 full factorial design. The concentrations of matrix forming polymers were selected as independent variables whereas lag time before drug release, drug release at 8, 12 and 20 h were selected as response variables. Tablets of optimized batch F5 containing 25% hydroxypropyl methyl cellulose K100M and 9% polyvinyl pyrrolidone K30 exhibited the maximum similarity with predicted drug release profile for an ideal formulation with similarity factor of 80.69. The lag time before drug release (5 h), drug release at 8 h (27.39%), 12 h (49.48%) and 20 h (86.69%) of optimized batch were close to predicted drug release profile for an ideal formulation. Drug release from optimized batch followed zero order kinetics with super case II transport. Optimized formulation was stable for 1 mo at environmental conditions of 40±2°C temperature and 75±5% relative humidity. Prepared drug delivery of propranolol hydrochloride may be useful to provide sustained drug release for 24 h at the site of absorption for chronotherapy of hypertension.